CHARACTERISTICS OF MORPHOPHENOTYPE AND PHYSICAL PERFORMANCE OF YOUNG FOOTBALL PLAYERS AND THEIR RELATIONSHIP TO PLAYING POSITION (LITERATURE REVIEW) - Sh. A. Mustafayeva (Scholar Express Journals, 2021)
Sportsmanship in football players is highly dependent on factors such as weight, body length, physical performance, speed and strength and speed. Physical performance is an expression of human performance, which has movement at its core. It manifests itself in various forms of muscular activity, and this in turn depends on the weakness and motivation of the person for professional activity. Anthropometric indicators weight, height, total dimensions and proportions of the body, somatotype, significantly influence physical performance, sports activity and the choice of sports specialization.
Keywords: Physical Performance; Peculiarities Of Morphophenotype; Young Football Players; Playing Role